Survival of probiotic bacteria in a whey cheese vector submitted to environmental conditions prevailing in the gastrointestinal tract - Madureira, A. R. (2010)
Various foods may be used to deliver probiotic bacteria into the gastrointestinal tract; one such example is Requeijão, a Portuguese whey cheese. Survival and stability of Bifidobacterium animalis strains BLC-1, Bb-12, and Bo, Lactobacillus acidophilus strains LAC-1 and Ki, L. paracasei ssp. paracasei strain LCS-1 and L. brevis strain LMG 6906 inoculated into Requeijão, when exposed to simulated gastrointestinal tract conditions, were assessed. Homogenates of inoculated whey cheese in 0.85% (w/v) sterile saline water were exposed to a solution of hydrochloric acid (pH 2.5–3.0) and pepsin (1000 unitsmL–1) at 371C, and then to 0.3% (w/v) bile salts after 60 or 120 min of acid exposure. All bacterial strains retained their initial viable cell numbers. Bifidobacterium animalis strains Bb-12 and Bo, and L. brevis strain LMG 6906 exhibited the highest viable cell numbers when exposed to bile salts, whereas the other strains had variable death rates.